Literasi Teknologi Informasi Untuk Meningkatkan Kompetensi Siswa Dalam Rangka Persiapan ANBK SDN 1 Surabaya Utara, Desa Surabaya Utara , Kec.Sakra Timur - Harianto; Fawwaz; Imam mahfuz hulaimi (Universitas Hamzanwadi, 2025)
Technology literacy training and typing skill development constitute a strategic initiative in preparing students to face the Computer-Based National Assessment (ANBK), particularly at SDN 1 Surabaya Utara, Sakra Timur District. Rapid technological advancement requires students not only to master academic content but also to possess fundamental competencies in using computer technology. In practice, however, a number of elementary school students still demonstrate limited familiarity with computers, both in terms of hardware recognition and basic operational skills. The training program discussed in this article was designed as a short, practical intervention encompassing an introduction to basic computer hardware—such as monitors, keyboards, mice, and CPUs—as well as typing exercises emphasizing correct spelling and writing conventions. The program was implemented through a gradual and interactive approach, allowing students to engage in hands-on practice. This method aimed to build students’ confidence in operating computers while simultaneously improving their typing accuracy and speed. The results indicate that the training program led to a significant improvement in students’ typing abilities and their understanding of basic computer technology. Students became more accustomed to using computer devices and demonstrated increased readiness to participate in ANBK. Therefore, technology literacy and typing skills training can be considered an effective supporting strategy for enhancing elementary school students’ preparedness to meet the demands of modern, technology-based learning and assessment environments